FIQIH UJROH DALAM BERDAKWAH - Achmad Yaman (STAI DI AL-HIKMAH, 2025)
The provision of compensation in da’wah (Islamic preaching) activities is not a new phenomenon; it has existed for a long time and occurs across various elements of society and religious activities. This phenomenon is evident in religious lectures delivered in both academic forums and public religious gatherings, where compensation is often given by event organizers to the ustadz or ustadzah who deliver the sermon. This qualitative study seeks to explain how Islam views the phenomenon of compensation in da’wah—commonly referred to as ujrah—from the perspective of the Arabic language, and how Muslim scholars articulate their opinions within the framework of Islamic jurisprudence (fiqh). The findings reveal that providing compensation or ujrah in da’wah and religious activities does not negate the sincerity (ikhlas) of the preacher, nor does it imply selling the verses of Allah for worldly gain. Rather, it serves as a form of respect and appreciation for the preacher who dedicates time and effort to teaching the community about their religion. The provision of compensation in da’wah activities reflects the principles of social exchange, in which da’wah—representing the transmission of religious values needed by society—acts as a stimulus that gives rise to compensation as a form of recognition within the social context of community life.